Fluvial, environmental and coastal developments in hydraulic engineering : proceedings of the International Workshop on State-of-the-Art Hydraulic Engineering, 16-19 February 2004, Bari, Italy /: proceedings of the International Workshop on State-of-the-Art Hydraulic Engineering, 16-19 February 2004, Bari, Italy. (©2004) - Unknown
No abstract available